2009
DOI: 10.1002/ijc.24731
|View full text |Cite
|
Sign up to set email alerts
|

Age distribution of human papillomavirus infection and cervical neoplasia reflects caveats of cervical screening policies

Abstract: Although a second age-related peak of human papillomavirus (HPV) infection is observed in many populations, it does not seem to have any impact on cervical screening policies. We examined the age-specific prevalence of HPV infection among 2,604 women enrolled for cervical screening and correlated the age at diagnosis of 2,491 cervical intraepithelial neoplasia Grade 2/3 (CIN2/3) lesions and 801 invasive cervical cancers (ICC). Two peaks of HPV infection were detected at 26-30 and 46-50 years, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 23 publications
5
39
3
1
Order By: Relevance
“…In a recent meta-analysis study, De Sanjosé et al reported that HPV prevalence, in women with normal cytology, declines with increasing age, but the authors estimated an increase of HPV infection for women aged 45-52 [28]. This observation was also reported by Chan et al in their recent study where they examined the age-specific prevalence of HPV infection among 2,604 women in Hong Kong [29]. The inverse age dependency has been observed in the Kingdom of Bahrain study where women positive for HPV were significantly older than women negative for HPV [30].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In a recent meta-analysis study, De Sanjosé et al reported that HPV prevalence, in women with normal cytology, declines with increasing age, but the authors estimated an increase of HPV infection for women aged 45-52 [28]. This observation was also reported by Chan et al in their recent study where they examined the age-specific prevalence of HPV infection among 2,604 women in Hong Kong [29]. The inverse age dependency has been observed in the Kingdom of Bahrain study where women positive for HPV were significantly older than women negative for HPV [30].…”
Section: Discussionmentioning
confidence: 76%
“…Women less than 34 years of age had significantly low risk of HPV infection in univariate and multivariate analysis. The literature data regarding the potential relationship between age and HPV infection are conflicting [27][28][29][30]. In a recent meta-analysis study, De Sanjosé et al reported that HPV prevalence, in women with normal cytology, declines with increasing age, but the authors estimated an increase of HPV infection for women aged 45-52 [28].…”
Section: Discussionmentioning
confidence: 99%
“…A change in the vaginal flora could also be an interesting cofactor and might be one explanation to the second age-related incidence peak (50-65) observed in many populations. 39 Although negative p16 immunostaining in the superficial layer is slightly more often associated with the non-HPV-16 subtype, most of the non-HPV-16 cases had weak or strong immunostaining in the superficial layer and some HPV-16 high-grade CINs also were negative. Thus, negative p16 in the superficial epithelial layers cannot be used as a definitive indication for non-HPV-16 infection.…”
Section: Cd8mentioning
confidence: 95%
“…Similar bimodal patterns are seen elsewhere in the developed world and may reflect a cohort effect associated with cervical cancer incidence. 10,11 Other possible explanations for this finding include increasing sexual activity of these older women or their sexual partners, or a decreased age-related immune response, possibly caused by hormonal changes related to menopause that result in a reactivation of latent HPV infection. [12][13][14] Despite the success of the cervical screening program, marked disparities continue to be observed in cervical cancer incidence and mortality between Indigenous and nonIndigenous Australia women.…”
Section: Cervical Cancermentioning
confidence: 99%